2021
DOI: 10.3390/ijerph182211917
|View full text |Cite
|
Sign up to set email alerts
|

Cooling Island Effect of Blue-Green Corridors: Quantitative Comparison of Morphological Impacts

Abstract: The patterns of green corridors in urban riverfront districts provide different synergistic cooling effects of blue-green space in urban areas. The purpose of this study is to quantify the spatial morphological impact of green corridors in riverfront block-scale area on the cooling effect. Three representative patterns (radiate, grid and dendritic) were selected in the study. The comprehensive influences analysis between multi-dimensional factors of spatial structure and morphology of green corridors and Ta (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
0
6
1
Order By: Relevance
“…Ultimately, the processed RCE contour was obtained. Jiang's method (Jiang et al 2021) was as reference to calculate RCI by computing the LST along the contour, and various indices of RCD were calculated using the minimum distance method. The study area was selected as the area within 1000 meters surrounding the Hangzhou section of the Grand Canal of Beijing-Hangzh ou , as the largest observed extent of RCE is 1000m (Su n et al 2012).…”
Section: River Cooling Effect Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, the processed RCE contour was obtained. Jiang's method (Jiang et al 2021) was as reference to calculate RCI by computing the LST along the contour, and various indices of RCD were calculated using the minimum distance method. The study area was selected as the area within 1000 meters surrounding the Hangzhou section of the Grand Canal of Beijing-Hangzh ou , as the largest observed extent of RCE is 1000m (Su n et al 2012).…”
Section: River Cooling Effect Calculationmentioning
confidence: 99%
“…In terms of land use types, the RCE effect in the case of a fixed water surface can be influenced by the vegetation proportion (Du et al 2016), as well as the size and connectivity of the green space. Irregularl y shaped areas and those that are parallel to the dominant wind direction with respect to the building space tend to receive a relatively high cooling effect from the river (Jiang et al 2021). A large-scale study of the Yangtze River basin in China identified six urban development and construction indicators that are closely linked to surface temperatu re changes in the riverfront area: percentage of vegetation area, distance from the river, bui lding density, building height, percentage of water area, and average green space patch area (Wang et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This NBS type allows a reduction in energy consumption and an increase in urban resilience [32][33][34]. The target of the NBS type "Accessible green corridors (PI)" is to make post-industrial sites and renatured river corridors accessible for local residents [35,36]. The NBS type "Local environmental compensation processes (EC)" aims to consider green infrastructures, NBS, and participatory co-design and co-implementation processes inherently into urban planning procedures starting at the local level of municipalities [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…High vegetation coverage can strengthen the cooling of riverbanks, and the maximum cooling occurs in places with a large number of trees covering and shading both sides of the banks [ 20 ]. The greenspace network mode with high connectivity is conducive to the cold air transportation of urban rivers to produce a better CI [ 21 , 22 ]. Interconnected greenspaces provide a higher CI to adjacent areas [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…At present, the commonly used software platforms are ENVI-met, fluent, WRF, Airpark, etc. Among them, ENVI-met is widely used to simulate the microclimate of different pattern of blue–green spaces [ 21 , 22 ]. However, the maximum simulation grid scale of ENVI-met software is limited to 2 km × 2 km, which is more suitable for the microscale [ 18 , 37 ].…”
Section: Introductionmentioning
confidence: 99%